(untitled) (diségno, 2026)
This paper investigates drawing as the critical epistemological bridge between the invisible laws of chemistry and the material realities of architecture. While chemists rely on graphic representation to render hidden molecular behaviors intelligible –from Bragg’s static lattice sketches to Matsumoto’s dynamic simulations– architects appropriate these same geometric codes to generate spatial form. We argue that drawing functions here as an “operative tool,” translating crystalline logic into three distinct structural typologies: spanning, compression, and inhabitation. The study traces this translation through three specific case studies. First, the truncated icosahedron of fullerenes (C60) provides a universal diagram for spanning, realized in Takaaki Bando’s bamboo artistic pavilions. Second, the self-interlocking, high-pressure lattices of Ice VI offer a speculative blueprint for compression, suggesting dense, vertical load-bearing systems for future infrastructure. Third, the “guest-host” chemistry of clathrate hydrates mirrors the metabolic logic of inhabitation, finding a powerful historical parallel in the permanent-transient structure of Kisho Kurokawa’s Nakagin Capsule Tower. By mapping this trajectory, we demonstrate that drawing is not merely representational but generative: it is the medium through which the invisible performance of molecules is transformed into the habitable logic of the built environment.